posted by Anonymous .
If (-2,y) is a solution to the equation 2x-3y=5, what is the value of y?
DIVIDE BOTH SIDES BY -3
NOW DO THE SAME FOR THE OTHER ONE PLUG THE -2 IN FOR X
PUT IN CALC WATCH SIGNS!!
All you have to do in this situation is substitute (-2) for the variable (x) in the equation. You can do this because all coordinates are of the form (x,y). Anything in the place of (x) can be seen as equal to (x). So, substituting, we can see:
2(-2) - 3y = 5
-4 - 3y = 5
-3y = 9
y = -3
As shown above, we can see that y = -3 when x = -2.